NEW OCEANIC PROXIES FOR PALEOCLIMATE - Henderson G.M. (My University, 2002)
Environmental variables such as temperature and salinity cannot be directly measured for the past. Such variables do, however, influence the chemistry and biology of the marine sedimentary record in a measurable way. Reconstructing the past environment is therefore possible by ‘proxy’. Such proxy reconstruction uses chemical and biological observations to assess two aspects of Earth’s climate system – the physics of ocean–atmosphere circulation, and the chemistry of the carbon cycle. Early proxies made use of faunal assemblages, stable isotope fractionation of oxygen and carbon, and the degree of saturation of biogenically produced organic molecules. These well-established tools have been complemented by many new proxies. For reconstruction of the physical environment, these include proxies for ocean temperature (Mg/Ca, Sr/Ca, δ44Ca) and ocean circulation (Cd/Ca, radiogenic isotopes, 14C, sortable silt). For reconstruction of the carbon cycle, they include proxies for ocean productivity (231Pa/230Th, U concentration); nutrient utilization (Cd/Ca, δ15N, δ30Si); alkalinity (Ba/Ca); pH (δ11B); carbonate ion concentration (foraminiferal weight, Zn/Ca); and atmospheric CO2 (δ11B, δ13C). These proxies provide a better understanding of past climate, and allow climate–model sensitivity to be tested, thereby improving our ability to predict future climate change. Proxy research still faces challenges, however, as some environmental variables cannot be reconstructed and as the underlying chemistry and biology of most proxies is not well understood. Few proxies have been applied to pre-Pleistocene times – another challenge for future research. Only by solving such challenges will proxies provide a full understanding of the range of possible climate variability on Earth and of the mechanisms causing this variability.